45, X/47, XXX Mosaicism and Short Stature. (7th June 2015) - Everest, Erica; Tsilianidis, Laurie A.; Haider, Anzar; Rogers, Douglas G.; Raissouni, Nouhad; Schweiger, Bahareh
Abstract : We describe the case of a ten-year-old girl with short stature and 45, X/47, XXX genotype. She also suffered from vesicoureteric reflux and kidney dysfunction prior to having surgery on her ureters. Otherwise, she does not have any of the characteristics of Turner nor Triple X syndrome. It has been shown that this mosaic condition as well as other varieties creates a milder phenotype than typical Turner syndrome, which is what we mostly see in our patient. However, this patient is a special case, because she is exceptionally short. Overall, one cannot predict the resultant phenotype in these mosaic conditions. This creates difficulty in counseling parents whose children or fetuses have these karyotypes.